65 EFFECTS OF PRENATAL EXPOSURE TO NICOTINE ON THE MISMATCH NEGATIVITY IN YOUNG INFANTS. (1st January 2005) - Lipmanson, R. C.; Davalos, D. B.; Hood, R.; Freedman, R.; Ross, R. G.
Abstract : Purpose: While prenatal exposure to nicotine has been found to be linked to a constellation of negative cognitive and behavioral outcomes in children and adults, it is unclear whether there are similar nicotine-related effects in early infancy. In this study, auditory temporal processing in young infants who had been exposed to nicotine in utero was compared to that of unexposed infants; it was hypothesized that the nicotine-exposed group would exhibit a diminished mismatch negativity (MMN) response. Methods: 25 infants (4 of whose mothers smoked and 21 of whose mothers did not smoke during their pregnancy) heard two series of tones in which the standard-interval series was randomly interrupted by tones at set deviant intervals, either "easy-to-detect" (50% temporal deviance) or "hard-to-detect" (15% temporal deviance). Evoked response potentials for the deviant tones were analyzed using the MMN paradigm. Results: For the "easy-to-detect" interval duration deviant, the mean MMN amplitude at Pz was significantly smaller for infants who were exposed to nicotine in utero than for those who were not, and this trend was observed at Cz for the "easy" deviant (Pz: t = -2.91, p = 0.014; Cz: t = -2.02, p = 0.074). Conclusions: Preliminary findings indicate that fetal nicotine exposure impairs auditory temporal processing in young infants. These results are likely to reflect long-term effects of fetal exposure to nicotine on the central nervous system, but may also be due to post-natal nicotine exposure. Further investigation with a larger sample size of infants whose mothers smoked during their pregnancy is recommended to verify these results.